Anti-lipogenic effect of Senna alata leaf extract in high-fat diet-induced obese mice - Jarinyaporn Naowaboot; Supaporn Wannasiri (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To examine the effect of Senna alata (S. alata) leaf extracts on the regulation of lipid metabolism in high-fat diet-induced obese mice. Methods: The obesity condition was induced in the male ICR mice by feeding them with high-fat diet (45 kcal% fat) for 12 weeks. At the 7th week of diet feeding, the obese mice were treated with the water extract of S. alata leaf at 250 and 500 mg/kg/day, respectively, that continued for six weeks. At the end of the treatment period, the biochemical parameters were determined. The hepatic histology and the gene and protein expressions were also examined. Results: In comparison with the obese control mice, the mice treated with S. alata showed a significant reduction in the elevated blood glucose levels and a decrease in the serum insulin and leptin levels. A reduction in the serum total cholesterol, triglyceride, non-esterified fatty acid, and hepatic triglyceride levels were also observed. The histological examination of the obese mice treated with S. alata showed a reduced lipid accumulation in the liver tissue. Hepatic lipogenic gene expression showed that S. alata decreased the activity of sterol regulatory element binding protein 1c, fatty acid synthase, and acetyl-CoA carboxylase. S. alata could suppress hepatic peroxisome proliferator-activated receptor gamma (PPARγ) protein. Moreover, the protein expression of PPARα in liver tissue was clearly increased by S. alata treatment. Conclusion: The treatment with S. alata could decrease several parameters of impaired lipid metabolism in the obese mice by downregulating sterol regulatory element binding protein 1c and PPARγ and upregulating PPARα. This study is the first report on the role of S. alata leaf extract in alleviating the abnormal lipid metabolism in obese conditions.